Application Perspectives of Nanomedicine in Cancer Treatment - Hou, Shanshan; Hasnat, Muhammad; Chen, Ziwei; Liu, Yinong; Faran Ashraf Baig, Mirza Muhammad; Liu, Fuhe; Chen, Zelong (Frontiers in Pharmacology, 2022)
Malignant tumor is a disease that seriously threatens human health. Based on the improvement of traditional treatment methods and the development of new treatment modes, the pattern of malignant tumor treatment is constantly being optimized. Nanomedicine plays an important role in these evolving tumor treatment modalities. In this article, we outline the applications of nanomedicine in three important tumor-related fields: chemotherapy, gene therapy, and immunotherapy. According to the current common problems, such as poor targeting of first-line chemotherapy drugs, easy destruction of nucleic acid drugs, and common immune-related adverse events in immunotherapy, we discuss how nanomedicine can be combined with these treatment modalities, provide typical examples, and summarize the advantages brought by the application of nanomedicine .